SPORT SHÍNÍǴÍWLARÍNA BEYIMLESIW - Iskenderov, T.Q.; Esemuratov, S.T.; Atajanov, K.I. (SCIENCE and SOCIETY, 2024)
The article defines the basic concepts of adaptation, the essence and functions of sports, gives a general description of adaptation during the period of the athletes’ training system, examines the means and methods, patterns of sports training and the principles based on them.